RACHEL MORSE’S NEGOTIATING AS THE EFFECT OF DOUBLE CONSCIOUSNESS IN DURROW’S THE GIRL WHO FELL FROM THE SKY - Lia Indri Hapsari (Kajian Linguistik dan Sastra, 2016)
Racism towards African-American brings many impacts to African-American people’s life, especially who have ever experienced it. One ofsome psychological effects that experienced by African-American is doubleconsciousness experience that could be explored in Durrow’s The Girl Who Fellfrom the Sky. Double consciousness phenomenon is found in the main characterof the novel named Rachel Morse, a daughter of white mother and African-American father, who has identity problem in her new society. This study aimsto attend the identity negotiation of Rachel as the result of double consciousnessshe experienced using double consciousness theory by W.E.B. Du Bois. Thisstudy reveals that Rachel Morse who experience double consciousness has tonegotiate her biracial identity in American society who still believe in ‘one-drop’rule so that she could fit in the society. The practice of racism and stereotypeforms need to be reduced to make a better living for African-American andbiracial people in the United States.